2019
DOI: 10.1080/10586458.2019.1636425
|View full text |Cite
|
Sign up to set email alerts
|

On Integers that are Covering Numbers of Groups

Abstract: The covering number of a group G, denoted by σ(G), is the size of a minimal collection of proper subgroups of G whose union is G. We investigate which integers are covering numbers of groups. We determine which integers 129 or smaller are covering numbers, and we determine precisely or bound the covering number of every primitive monolithic group with a degree of primitivity at most 129 by introducing effective new computational techniques. Furthermore, we prove that, if F 1 is the family of finite groups G su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Refer to Theorem 1.3(4) for a summary of the results on A(n, q 1 , q 2 ). Our strategy is based on the approach used to prove [15,Theorem 1.7], where it is shown that for n = 2, the group AGL(n, q) has covering number (q n+1 − 1)/(q − 1). However, our formulas for σ(A(n, q 1 , q 2 ))-and the methods used to establish themare more complicated than in the group case.…”
Section: Frequently Used Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Refer to Theorem 1.3(4) for a summary of the results on A(n, q 1 , q 2 ). Our strategy is based on the approach used to prove [15,Theorem 1.7], where it is shown that for n = 2, the group AGL(n, q) has covering number (q n+1 − 1)/(q − 1). However, our formulas for σ(A(n, q 1 , q 2 ))-and the methods used to establish themare more complicated than in the group case.…”
Section: Frequently Used Resultsmentioning
confidence: 99%
“…Proof. The proof is essentially identical to that of [15,Lemma 5.1] and [31,Lemma 3.1] with the word "group" changed to the word "ring," but it is included for the sake of completeness. Let D and Π be as in the statement of the lemma, and assume that c(M) 1 for all maximal subrings not in D; the proof with strict inequalities is analogous.…”
Section: 2mentioning
confidence: 94%
See 1 more Smart Citation
“…Theorem 3.4. (Garonzi [10]; Garonzi, Kappe and Swartz [11]) The following list identifies exactly which integers less than 130 that are not covering numbers: The corollary below proves that for each k ∈ Z + , there exists a group G such that ι(G) = k.…”
Section: Nilpotent Groupsmentioning
confidence: 99%
“…The remaining case was confirmed by Detomi and Lucchini [6], who proved that there is no group G with σ(G) = 11. Additionally, the combined results of Garonzi, Kappe, and Swartz [10,11] classified every integer less than 130 that is a covering number of some nontrivial group. More generally, the structure of groups G containing no normal nontrivial subgroup N such that σ(G/N) = σ(G) was investigated by Detomi and Lucchini [6].…”
Section: Introductionmentioning
confidence: 99%